A study on the inhibition of mild steel corrosion in hydrochloric acid by pyridoxol hydrochloride - James,A. O. (2007)
The inhibition of the corrosion of mild steel in 2M hydrochloric acid solutions by Pyridoxol hydrochloride (PXO) has been studied using weight loss and hydrogen evolution techniques. The inhibitor (PXO) exhibited highest inhibition efficiency of 71.93% at the highest inhibitor concentration of 1.0 x 10-2M investigated and a temperature of 303K from weight loss result. Also, inhibition was found to increase with increasing concentration of the inhibitor and decreasing temperature. A first order type of mechanism has been deduced from the kinetic treatment of the weight loss results and the process of inhibition attributed to physical adsorption. The results obtained from the two techniques show that pyridoxol hydrochloride could serve as an effective inhibitor of the corrosion of mild steel in HCl acid solution. The compound obeys the Langmuir adsorption isotherm equation.